Synthesis and Crystal Structure of MnL3·(ClO4)2(L = Diacetyl dihydrazone). - BI, JIAN-HONG; Xian-Huang, Zi-; LI, MENG (Asian Journal of Chemistry, 2010)
A new complex MnL3·(ClO4)2 (L = diacetyl dihydrazone) has been synthesized and characterized by IR spectra, elemental analysis and single-crystal X-ray. The crystal is trigonal, space P-3c1 with unit cell parameters: a = 9.6546(4)Å, b = 9.6546(4)Å, c = 15.3525 (11)A, α = 90º, β = 90º, γ = 120º, V = 1239.30(11)Å3, Z = 2, Mr = 596.32, Dc = 1.598 Mg/cm3, μ = 0.811 mm-1, F(000) = 618, T = 293(2) K, R = 0.0481, wR = 0.1627 for 3899 reflections with I > 2σ(I).